South - Sir Ernest Shackleton's Glorious Epic Of The Antarctic (United Kingdom, 1919)
Photographed by Frank Hurley, South is the film record of Sir Ernest Shackleton's heroic but ill-starred attempt to cross Antarctica in 1914-16. It is both a unique historical document, and a tribute to the indomitable courage of a small party of men who set out on a voyage of discovery that turned into an epic struggle for survival. This restored version of the film has been constructed by the National Film and Television Archive from a wide range of materials. The NFTVA has applied its own tinting and toning to match the original prints, and has produced this handsome and richly coloured testament to a remarkable episode in the history of exploration.